Activity of cell-free supernatant from Sponge associated bacteria against the growth and bacterial adhesion of microfouling Bacteria - Satheesh, Sathianeson; Abdulrahman, Idris; El-Sherbiny, Mohsen; Satheesh, Sathianeson (Journal of King Abdulaziz University: Marine Sciences, 2023)
This study was carried out to evaluate the activity of cell free supernatant (CFS) from sponge associated bacteria against the growth and bacterial adhesion of biofilm bacteria. A sponge was collected from the Red Sea by Scuba diving and identified as Hyrtios erectus. After washing and cleaning to remove loosely attached bacteria, endophytic bacteria were isolated from the sponge by serial dilution method using Zobell Marine Agar (ZMA) as growth medium. Pure culture of the bacteria obtained were then identified by 16s rRNA gene sequencing method. The cell free supernatant (CFS) from two strains of bacteria isolated from the sponge were subjected to bacterial growth inhibition and bacterial adhesion inhibition assay using bacterial growth inhibition assay method and microtiter plate assay method respectively against four microfouling bacteria. The two organisms were identified as Idiomarina sp. MS-E2 and Staphylococcus edaphicus MS-E4. Both organisms show potential inhibition activity against the tested biofilm bacteria by inhibiting their growth and adhesion ability. This is an indication of the role of the sponge associated bacteria in producing compounds with potential activity against bacterial adhesion to surfaces.